2022
DOI: 10.21203/rs.3.rs-2050378/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of LongdanXiegan Decoction on the Treatment of chronic prostatitis: A Systematic Review and Meta-Analysis

Abstract: Background: Chronic prostatitis (CP) is one of the most common diseases in urology. Longdanxiegan decoction (LDXGD), a classical formula of traditional Chinese medicine (TCM), has been widely used for chronic prostatitis patients with the damp invasion of lower energizer syndrome in China, and the effects were satisfactory. However, there is still no clear understanding of its clinical effects. Purpose: This study aimed to systematically evaluate the efficacy and safety of LDXGD for chronic prostatitis. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[17] A meta-analysis on the effectiveness and safety of Qingzhuo Qudu Pill, which included 679 patients, showed that Qingzhuo Qudu Pill improved the total effectivity rate and reduced the NIH-CPSI score, and it was safe. [18] Zhang et al [19] randomly divided CP/CPPS 240 patients with kidney deficiency and blood stasis syndrome into the TCM, Western medicine, and combined groups. Eighty cases in each group were given Yishen Tongluo prescription, Pushitai tablet, and Yishen Tongluo prescription combined with Pushitai tablet, respectively.…”
Section: Chinese Herbal Decoctionmentioning
confidence: 99%
“…[17] A meta-analysis on the effectiveness and safety of Qingzhuo Qudu Pill, which included 679 patients, showed that Qingzhuo Qudu Pill improved the total effectivity rate and reduced the NIH-CPSI score, and it was safe. [18] Zhang et al [19] randomly divided CP/CPPS 240 patients with kidney deficiency and blood stasis syndrome into the TCM, Western medicine, and combined groups. Eighty cases in each group were given Yishen Tongluo prescription, Pushitai tablet, and Yishen Tongluo prescription combined with Pushitai tablet, respectively.…”
Section: Chinese Herbal Decoctionmentioning
confidence: 99%